Welding Quality Control Using The Sqc (Statistical Quality Control) Method In An Effort To Minimize The Occurrence Of Rejects At Pt.Xyz - Novita Ramadayanti; Akmal Suryadi (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
PT. XYZ is an international company operating in the energy sector, especially oil and gas, with a focus on fabrication and construction activities for large-scale projects. One of the main production processes that is very influential is welding. To ensure welding quality, PT. XYZ uses the Non-Destructive Testing – Ultrasonic Testing (NDT-UT) method. However, during the inspection process, problems are often found in the form of rejects due to defects that do not meet welding quality standards. Some types of defects detected include LOF (Lack of Fusion), LOP (Lack of Penetration), and ESI (Excessive Spatter Inclusion). This research aims to determine the percentage of the most dominant welding defects, identify factors that cause defects, and provide recommendations for improvements to improve welding quality. The method used is Statistical Quality Control (SQC) with the help of tools such as check sheets, histograms, Pareto diagrams, scatter diagrams, control charts and fishbone diagrams. Based on the data collected, a LOF defect of 5,434 mm was found, an ESI defect of 1,990 mm, and an LOP defect of 1,030 mm. SQC analysis shows that the dominant defect is LOF with a percentage of 64%. The main causal factors come from methods, humans, machines and materials. Therefore, companies need to make improvements and developments to reduce product defects so that they can improve welding quality.